Parental care for developing character of children - Sugiarti, Rini; Erlangga, Erwin (Edelweiss Applied Science and Technology, 2025)
Character development in youngsters occurs during their initial life phases. As the smallest unit of society, parents have a crucial impact on this development. Through their parental care, parents play a vital role in shaping behaviors that are essential for future living. The actions demonstrated by children reflect their character, which is pivotal in determining their future quality of life. The aim of this research was to empirically investigate the indicators of character development in children. The sample comprised 456 students from Semarang. To uncover the character development indicators among students, two scales were utilized: the character development scale and the parenting scale. In this study, confirmatory factor analysis (CFA) was the method employed to assess the validity of the indicator variables. Findings from this research reveal a significant relationship between parenting practices and the development of character in children. The character traits instilled in children at home form the essential groundwork for their adult lives in the broader community. Additionally, the research indicates that the character development of junior high school students in Semarang can be facilitated by parental guidance that emphasizes collaboration, acceptance, affection, tranquility, esteem, and consciousness as demonstrations of behavior.